Histologi Kardiovaskular pada Wistar Diabetes Melitus Tipe 2 dengan Curcuma Zedoria - Antonius Fransiskus Putra Meliala; Christopher Lawrence; Andreas Xaverio Bangun; Sondang Silitonga (SCIENTIA JOURNAL, 2024)
Type 2 Diabetes Mellitus (T2DM) can cause significant cardiovascular damage, including diabetic cardiomyopathy and diabetic vasculopathy, associated with increased oxidative stress and inflammation. This study aimed to evaluate the effect of Curcuma zedoaria extract on the improvement of heart and aorta histopathology in Wistar rats with T2DM. C. zedoaria extract was administered orally at doses of 100, 200, and 400 mg/kgBW for 6 weeks. The results showed that administration of C. zedoaria extract significantly reduced heart fibrosis and aortic elastin fragmentation, particularly at the 400 mg/kgBW dose. These findings suggest that C. zedoaria has potential as an adjunctive therapy to prevent cardiovascular damage in T2DM, with mechanisms involving the inhibition of oxidative stress and inflammation.